A Late-Diagnosed Case of Common Variable Immunodeficiency - Coşkun Doğan; Nurhan Kasap; Cihan Örçen (Ahi Evran Medical Journal)
Common Variable Immunodeficiency (CVID) is the most common form of primary immunodeficiency (PID). CVID is characterized by decreased serum immunoglobulin levels, decreased or absent antibody production, and normal or low B-lymphocyte counts. It has a wide variety of clinical presentations, including recurring infections, inflammatory diseases, gastrointestinal diseases, lymphoid hyperplasia, granulomatous diseases, cytopenias, progressive lung diseases, and non-communicable diseases such as cancer. The main treatments are antibiotic prophylaxis and immunoglobulin replacement therapy. In this case report, a 62-year-old patient with a medical history of pneumonia that had recurred at least six times in the last five years, one of which required hospitalization, a history of pulmonary thromboembolism, and a 10-day intensive care unite stay, lymphoproliferation, and a diagnosis of CVID as a result of further examinations is presented.